2022
DOI: 10.3390/ph15111369
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal and Cytoskeleton-Associated Proteins: Key Regulators of Cancer Stem Cell Properties

Abstract: Cancer stem cells (CSCs) are a subpopulation of cancer cells possessing stemness characteristics that are closely associated with tumor proliferation, recurrence and resistance to therapy. Recent studies have shown that different cytoskeletal components and remodeling processes have a profound impact on the behavior of CSCs. In this review, we outline the different cytoskeletal components regulating the properties of CSCs and discuss current and ongoing therapeutic strategies targeting the cytoskeleton. Given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 306 publications
0
2
0
Order By: Relevance
“…Because geranylgeranylation of Rho GTPases is fundamental for their downstream effects on cytoskeletal reorganization ( 20 ), which mediates the interaction of cancer stem cells (CSC) with the tumor microenvironment, maintenance of stemness, and CSC migration ( 21 ) we next tested which Rho GTPase would affect the self-renewal capacity of GBM cells ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Because geranylgeranylation of Rho GTPases is fundamental for their downstream effects on cytoskeletal reorganization ( 20 ), which mediates the interaction of cancer stem cells (CSC) with the tumor microenvironment, maintenance of stemness, and CSC migration ( 21 ) we next tested which Rho GTPase would affect the self-renewal capacity of GBM cells ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Since previous studies established differential expression levels of chorein in the three rhabdomyosarcoma cell lines ( Honisch et al, 2015b ), our present observations may pointing out a possible correlation between chorein expression levels and interaction to the microtubular network. Conversely, previous studies established that reorganization of cytoskeletal structures including actin microfilaments and modulation of cytoskeletal gene signaling in tumor cells may regulate pivotal cellular functions including cell survival and motility ( Yamazaki, Kurisu & Takenawa, 2005 ; Yilmaz & Christofori, 2009 ; Jaya, 2020 ; Ong et al., 2020 ; Li et al., 2022 ). Accordingly, our study indicates that the microtubule reorganization might contribute to the reported regulation of apoptosis in rhabdomyosarcoma cells upon chorein silencing, as described before ( Honisch et al, 2015b ).…”
Section: Discussionmentioning
confidence: 98%